Protection of minority shareholders’ rights in group of companies: Lithuania and EU company law perspectives - Bakanauskas, Edvinas (Vilnius University Open Series, 2020)
Just as in the entire European Union, in Lithuania company groups are an integral part of the modern business world. It is the companies that are part of company groups are leading both in Lithuania and in the European Union in terms of a number of economic indicators: revenues, number of employees, amounts of taxes paid and other contributions. Despite being an integral part of modern business, regulation of company groups has not yet attracted sufficient attention both at the European Union or the national level. Such absence of a consistent regulation may lead to or cause, inter alia, infringements of rights of minority shareholders. Accordingly, the purpose of the present article is to assess whether the effective Lithuanian or European Union regulation is sufficient to protect minority shareholders’ rights in group of companies.